Socio-economic impact of European singel market on Lithuanian companies: Methodology manual - Hannu Hernesniemi; Pekka Lindroos (The Research Institute of the Finnish Economy (ETLA), 2000)
This report has been written within the framework of the Phare SEIL (Support for European Integration in Lithuania) project supporting the Government of Lithuania in preparations for the accession to the European Union. The manual summarises the method used and developed when drafting separate impact studies for the most important industries of Lithuania. The industries examined are the wood, foodstuffs, textile and clothing and road transport industries. Reports were drafted by Lithuanian experts from Eurofaculty at Vilnius University, under the supervision of the authors and Dr. Mark Chandler. Three other reports are forthcoming, covering the chemical, construction products and (a joint report about) the electronic and machinery manufacturing industries under the supervision of Professor Robertas Jucevicius of the Kaunas University of Technology. The social impacts of the European Single Market very much depend on the competitiveness of the industries. We put a lot of emphasis on benchmarking the performance of industries and studying carefully their competitiveness and the most important factors behind it. To do so, the cluster approach was used. In order to increase the influence of the studies, we tied industry organisations and industrial policy officials, together with the researchers, to identify the strategic development needs of industries and make policy proposals for improving the competitiveness of the industries concerned. The other part of the analysis was the regulatory changes (new directives regulating the firms, abolishment of border formalities, etc.) and their direct costs and benefits. The direct effects of integration mean costs and incomes now. But it is important to realise that these regulatory changes mean that the size of the real costs, including those over the long-term, depend on the level of competitiveness and development activities. Along with the competitiveness pyramid of the European Commission we developed suggestions for main indicators measuring the socio-economic impacts of EU membership, which can be used also for other applicant countries. – Lithuania ; EU membership ; socio-economic impacts ; competitiveness – – Raportti tuotettiin osana Phare SEIL –projektia (Support to European Integration in Lithuania), jolla tuettiin Liettuan hallitusta Liettuan valmistautuessa EU-jäsenyyteen. Manuaali kokoaa menetelmät, joita käytettiin ja kehitettiin, kun tehtiin tutkimukset jäsenyyden vaikutuksista neljään Liettuan kannalta tärkeimpään toimialaan. Nämä alat ovat elintarviketeollisuus, tekstiili- ja vaatetusteollisuus, puunjalostus ja maantiekuljetukset. Raporttien tekijät ovat Vilnan yliopiston Eurotiedekunnasta. Heitä ohjasivat manuaalin kirjoittajat ja tohtori Mark Chandler. Kolme uutta raporttia – raportit kemianteollisuudesta, rakennustuoteteollisuudesta sekä yhteinen raportti sähkö- ja elektroniikkateollisuudesta ja koneenrakennuksesta on tekeillä Kaunasin teknillisessä yliopistossa Professori Robertas Jucevicius:n johdolla. Yhteismarkkinoiden sosiaaliset vaikutukset riippuvat keskeisesti toimialojen kilpailukyvystä. Niinpä keskityimme toimialojen benchmarkkaukseen ja niiden kilpailukyvyn ja siihen vaikuttavien tekijöiden tutkimiseen. Tässä käytimme klusterianalyysiä. Tutkimusten vaikuttavuuden lisäämiseksi niihin kytkettiin mukaan toimialajärjestöjä ja elinkeinopolitiikasta vastaavia virkamiehiä. He yhdessä tutkijoiden kanssa tunnistivat toimialojen strategisia kehitystarpeita ja tekivät ehdotuksia aloja kehittävistä elinkeinopoliittisista toimenpiteistä. Analyysin toinen osa oli säännöksissä tapahtuvien muutosten (uudet direktiivit, rajamuodollisuuksien poistuminen jne.) vaikutusten arviointi. Nämä tuovat heti suoria kustannuksia ja hyötyjä. On kuitenkin tärkeä huomata, että uusista säännöksistä aiheutuvat todelliset kokonaiskustannukset, mukaan lukien pitkän ajan kustannukset, riippuvat alojen kilpailukyvystä ja sen kehittämiseksi tarvittavista toimenpiteistä. Manuaalissa teemme myös Euroopan Komission esittämää kilpailukykypyramidia noudattelevan ehdotuksen indikaattoreista, joilla voidaan mitata EU-jäsenyyden yhteiskunnallis-taloudellisia vaikutuksia hakijamaissa. – Liettua ; EU-jäsenyys ; yhteiskunnallis-taloudelliset vaikutukset ; kilpailukyky
Keywords: 330; Internationaler Wettbewerb; EU-Binnenmarkt; Litauen